Analysis of Supply Chain And Value Chain On Smoked Manyung Fish To Increase Sales On “Asap Indah” Fish Production Center Wonosari Village Demak - Niken Siswaningsih; Pramudi Arsiwi; Tita Talitha (OPSI, 2021)
Fish Production Center “Asap Indah” is one of the production centers in Demak, which specializes in processing fresh fish into semi-processed products, smoked fish. To support the sustainability of product distribution, supply chain management is needed to oversee the process from procurement of raw material to distribution to final consumers. Therefore, a comprehensive supply chain management analysis is necessary to increase sales and establish effective distribution channels. This research aims to understand the existing value chains of smoked manyung fish, the added value of each contributor on value chains, and to determine the most effective distribution channels of smoked manyung fish. The method used for data processing is descriptive-analytic SCM, Value Chain, and Value Added method. The result of this research, based on value-added calculation analysis using the Hayami method, shows fresh fish wholesalers give the least added value to the product or have the least amount of activities, so decreasing the unproductive activity to lower production cost is recommended. Value chain analysis shows that distribution channels or the most effective selling method of smoked fish are direct selling to the final consumer,accompanied by developing vacuum packaging to increase consumers’ interest in the product.